2008
DOI: 10.1056/nejmoa0706930
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Therapy after Traumatic Brain Injury in Children

Abstract: In children with severe traumatic brain injury, hypothermia therapy that is initiated within 8 hours after injury and continued for 24 hours does not improve the neurologic outcome and may increase mortality. (Current Controlled Trials number, ISRCTN77393684 [controlled-trials.com].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
275
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 603 publications
(301 citation statements)
references
References 27 publications
8
275
0
5
Order By: Relevance
“…Obtaining informed consent for research in critically ill patients involves a complex interplay between patient, legal guardian, consent process, and study-related factors. A review of the literature showed limited data on the consent process and consent rates in pediatric critical care research which have varied from 42 to 94% in recent large trials [4][5][6][7][8]. The factors that affect these consent rates are poorly understood and may lead to delays in trial completion and obtaining results that may influence patient care [6], difficulty with planning and financing of clinical studies [4], and questions about the reliability and generalizability of trial results [7].…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining informed consent for research in critically ill patients involves a complex interplay between patient, legal guardian, consent process, and study-related factors. A review of the literature showed limited data on the consent process and consent rates in pediatric critical care research which have varied from 42 to 94% in recent large trials [4][5][6][7][8]. The factors that affect these consent rates are poorly understood and may lead to delays in trial completion and obtaining results that may influence patient care [6], difficulty with planning and financing of clinical studies [4], and questions about the reliability and generalizability of trial results [7].…”
Section: Introductionmentioning
confidence: 99%
“…44 Another recently published study on hypothermia in pediatric brain injury, which cooled for only 24 hours and then rewarmed regardless of ICP, showed a negative effect of the intervention on functional outcomes. 45 Indeed, given what is known about rebound increases in ICP and timing of cerebral edema, it is not surprising that this protocol was found to be harmful. It would be of great value for Western researchers to attempt to reproduce the success of prophylactic long-term hypothermia achieved in Asia, where most of the long-term cooling studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large, multicenter, randomized, placebocontrolled trial involving 225 children with severe TBI (GCS≤8) did not reveal a difference between groups, with a tendency toward worse outcome in the hypothermia group (mean temperature, 33.1°C ± 1.2°C) due to a higher mortality rate in patients >7 years of age [112]. A current ongoing trial enrolling children <16 years of age is attempting to show benefit by extending the cooling period (32°C to 33°C) to 48 h with a slow re-warming phase of 1°C every 12 to 24 h [113].…”
Section: Tbimentioning
confidence: 99%